2007
DOI: 10.1073/pnas.0611302104
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock-inducible Cre/Lox approaches to induce diverse types of tumors and hyperplasia in transgenic zebrafish

Abstract: RAS family members are among the most frequently mutated oncogenes in human cancers. Given the utility of zebrafish in both chemical and genetic screens, developing RAS-induced cancer models will make large-scale screens possible to understand further the molecular mechanisms underlying malignancy. We developed a heat shock-inducible Cre/Lox-mediated transgenic approach in which activated human kRASG12D can be conditionally induced within transgenic animals by heat shock treatment. Specifically, double transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 39 publications
(42 reference statements)
5
125
1
Order By: Relevance
“…To capitalize on the powerful developmental and genetic tools available in zebrafish, researchers have created numerous zebrafish tumor models (Langenau et al, 2003Yang et al, 2004;Berghmans et al, 2005;Patton et al, 2005;Haramis et al, 2006;Sabaawy et al, 2006;Le et al, 2007). The ultimate goal of the majority of this work is to identify pathways that modify disease states.…”
mentioning
confidence: 99%
“…To capitalize on the powerful developmental and genetic tools available in zebrafish, researchers have created numerous zebrafish tumor models (Langenau et al, 2003Yang et al, 2004;Berghmans et al, 2005;Patton et al, 2005;Haramis et al, 2006;Sabaawy et al, 2006;Le et al, 2007). The ultimate goal of the majority of this work is to identify pathways that modify disease states.…”
mentioning
confidence: 99%
“…2, a larger number of hematoxylin-stained cells was detected at the tumor site of DEN-treated zebrafish compared to that in control zebrafish. In addition, tumor sections showed less eosin-staining efficiency than normal tissue, suggesting that rapidly dividing cells, such as cancer cells, are less prone to staining, as reported by Le et al (2007). The DHE staining to visualize ROS showed that normal muscle exhibited a stronger red intensity due to eosin staining and fewer nuclei compared with those in tumor tissue, which had a larger number nuclei of increased size with weaker red staining intensity (Fig.…”
Section: Histological Analysismentioning
confidence: 77%
“…To generate the ␤-actin-loxPDsRed-loxP-EGFP construct, a 2.7-kb zebrafish ␤-actin promoter was excised from ␤-actin-loxP-EGFP-loxPkRASG12D plasmid (Le et al, 2007) by BamH I and Xho I, and blunted with Klenow fragment of E. coli DNA polymerase I., then cloned into the blunt-ended Xba I site of loxP-DsRed-SV40-loxP-PBSK-I-sceI plasmid (M. Deng et al, unpublished data). Finally, EGFP-SV40 fragment was excised from pCS2 ϩ -EGFP by Cla I and Kpn I and ligated into the same sites of ␤-actin-loxP-DsRed-loxP-PBSK-IsceI plasmid.…”
Section: Constructsmentioning
confidence: 99%
“…On the other hand, a heat-shock promoter-driven Tg(HSP70:EGFP-Cre) transgenic line was established and demonstrated to be able to mediate recombination when mated with a test line Tg (CMV:loxH-STOP-loxP-EGFP) after heat shock induction at 42°C (Thummel et al, 2005). Recently, Look's and Zon's groups reported that heat-shock promoter-driven Cre transgenic fish is able to induce DNA recombination in zebrafish adult, resulting in overexpression of oncogenic c-Myc or kRASG12D in the developing lymphoid cells and entire animal, respectively, and the subsequent development of T-cell acute lymphoblastic leukemia and hyperplasia in multiple tissues or tumors such as myeloproliferative disorder and rhabdomyosarcoma (Feng et al, 2007;Le et al, 2007). In spite of this progress, it remains unknown whether Cre recombinase is functional when expressed in a tissue-and/or cell subtype-specific manner.…”
Section: Introductionmentioning
confidence: 99%